The n

^{th}term of the progression (frac{4}{2}), (frac{7}{3}), (frac{10}{4}), (frac{13}{5}) is …-
**A.**

(frac{1 – 3n}{n + 1}) -
**B.**

(frac{3n + 1}{n + 1}) -
**C.**

(frac{3n + 1}{n – 1}) -
**D.**

(frac{3n – 1}{n + 1})

##### Correct Answer: Option B

##### Explanation

Using T_{n} = (frac{3n + 1}{n + 1}),

T_{1} = (frac{3(1) + 1}{(1) + 1} = frac{4}{2})

T_{2} = (frac{3(2) + 1}{(2) + 1} = frac{7}{3})

T_{3} = (frac{3(3) + 1}{(3) + 1} = frac{10}{4})

There is an explanation video available below.